NARSISISTIK XARAKTERGA EGA BO'LGAN SHAXSNING XATTI-HARAKATLARINING O'ZIGA XOS XUSUSIYATLARI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, the author examines the theoretical aspects of the behavior of people with a narcissistic personality type and presents the results of the diagnosis of narcissistic personality traits using the Deneke and Hilgenstock Narcissism Assessment Test.